2019
DOI: 10.22159/ajpcr.2019.v12i18.33721
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Self-Medication Practices in an Urban Community

Abstract: Objective: This study was conducted with the aim to assess the knowledge and attitude of self-medication practices among the residents of an urban community. Methods: A cross-sectional, observational study was conducted among 270 participants for the duration of 6 months using a semi-structured questionnaire which consisted of the domains of knowledge and attitude. Logistic regression was used for drawing statistical inferences. Results: The prevalence of self-medication was found to be 37.04%. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…As India is one of the highest populated countries with diversified customs health care related topics and studies should be focused on strong determination. Population has been also taking drugs in pharmacies without prescription, which has chances to increase in DRPs [15]. In this research we were also observed inappropriate utilization of antibiotics; this also very serious issue may causes to bacterial resistance according to Herawati et al [16].…”
Section: Discussionsupporting
confidence: 55%
“…As India is one of the highest populated countries with diversified customs health care related topics and studies should be focused on strong determination. Population has been also taking drugs in pharmacies without prescription, which has chances to increase in DRPs [15]. In this research we were also observed inappropriate utilization of antibiotics; this also very serious issue may causes to bacterial resistance according to Herawati et al [16].…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, studies in Malaysia and Oman had reported high usage of internet for searching health information (85.7% and 89%, respectively) [29,30]. This may be attributed to the convenience of retrieving information from the internet as current university students are a new breed of millennials who are digital natives and have been trained to use electronic devices since young age [30,31]. However, the concern is the ability of university students to identify reliable sources of information and to interpret them correctly to overcome their health conditions [9].…”
Section: Discussionmentioning
confidence: 99%
“…Pekerjaan sehari-hari yang dilakukan oleh ibu rumah tangga yakni menyapu, mengepel, membersihkan kamar mandi, mencuci pakaian, setrika, mencuci piring, memasak, berkebun dan mengurus anak menyebakan spasme dan strain pada otot (Nugraha, dkk., 2020). Semua kegiatan tersebut mengharuskan tubuh untuk membungkuk, memutar gerakan, mengangkat, menarik benda yang berat dan duduk dengan posisi tidak benar (Gupta, 2011).…”
Section: Hasil Dan Pembahasanunclassified